Agronomic performance in Paspalum interspecific hybrids subjected to nitrogen application rates or in mixture with temperate legumes - Motta, Eder Alexandre Minski da (2018)
Plicatula is a taxonomic group within of the genus Paspalum that contains interesting species considering their phenotypic diversity for forage traits, and some of these species have been improved through artificial interspecific hybridization. Nitrogen (N) is an important limiting factor to produce biomass. Forage legumes contribute with symbiotic N2 fixation and can increase biomass yield and the nutritive value of the pastures. The objectives of this thesis were: (i) evaluate dry matter yield (DMY), N use efficiency (NUE), nutritive value, cold tolerance and plant persistence in hybrids of Paspalum plicatulum x P. guenoarum subjected to N application rates, (ii) compare biomass yield and nutritive value of the grass–legume system to a grass–N fertilizer system, and (iii) select the best hybrids for new steps within the breeding program. The study was conducted from September 2015 to May 2017. The experimental design was a randomized complete block in split-plot arrangement with three replicates. Treatments were five N rates (0, 60, 120, 240, and 480 kg N ha-1 N), and one grass-legumes mixture (Trifolium repens + Lotus corniculatus) as whole plots, and six genotypes (1020133, 102069, 103084, 103061, P. guenoarum ecotype Azulão and Megathyrsus maximus cv. Aruana used as a control) as subplots. Nitrogen rates of 240 and 480 kg N ha-1 increased Total-DMY, Leaf-DMY, cold tolerance and persistence but decreased NUE. Higher NUE was obtained with N rates between 60 and 120 kg N ha-1. Total-DMY for grass-legume mixture was similar to the N rates of 60 and 120 kg N ha-1. Hybrid 1020133 had Total-DMY similar to Azulão and Aruana, as well as Leaf-DMY greater than Aruana. Hybrid 1020133 showed greater cold tolerance and exhibited greater NUE at 60 kg N ha-1 than the other genotypes. At the N rate of 480 kg N ha-1 increased crude protein (27%) and digestibility (4%) and decreased neutral (6%) and acid (7%) detergent fiber compared to the 0 kg N ha-1. Grass-legume mixture showed greater nutritive value compared to N-fertilized grass. Hybrid 103061 had greater crude protein and digestibility and lower neutral and acid detergent fiber than Azulão and Aruana. Therefore, there is opportunity to increase DMY, NUE, cold tolerance and plant persistence, and improve the nutritive value through genotype selection and N management. In addition, grass-legume mixture showed greater nutritive value than N-fertilized grass and can be an alternative practice to replace to the application of N fertilizer up to the rate of 120 kg N ha-1. Hybrids 1020133 and 103061 should be indicated for new studies, such as seed production and animal performance.